2019
DOI: 10.1177/1474022219831613
|View full text |Cite|
|
Sign up to set email alerts
|

Creative economy, cultural economics and entrepreneurship – Questions for a masters programme in its adolescence. An Interview with Mariangela Lavanga and Ellen Loots

Abstract: The purpose of this interview is to discuss the aims, objectives and achievements of a pioneering European masters degree -in the context of the politics of higher education and the economics of the creative industries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 10 publications
0
2
0
1
Order By: Relevance
“…In the context of global entrepreneurship education policies, it has become evident that globalization has facilitated the definition of such policies globally (Datta, 2015;Jardim, 2022b;Vickery, 2019). It was found that synergistic collaboration between different local actors -universities, industry and governments -is essential for creating entrepreneurial ecosystems.…”
Section: Discussionmentioning
confidence: 99%
“…In the context of global entrepreneurship education policies, it has become evident that globalization has facilitated the definition of such policies globally (Datta, 2015;Jardim, 2022b;Vickery, 2019). It was found that synergistic collaboration between different local actors -universities, industry and governments -is essential for creating entrepreneurial ecosystems.…”
Section: Discussionmentioning
confidence: 99%
“…Researches conducted in various fields undoubtedly confirm these facts, because as many as 60% of companies stated affirmatively in terms of the success of the application of information technologies, about 30% partially agree, while only 10% believe that modern information and communication technologies should not be used (Vickery et al., 2019). A very important function of information systems in the company's operations is the ability to analyze financial operations and accordingly take corrective actions in a timely manner.…”
Section: Information Technologies In Business Organizationsmentioning
confidence: 97%
“…Ovako primenjen sistem olakšava i donošenje poslovnih odluka. Istraživanja sprovedena u različitim oblastima nesumnjivo potvrđuju ove činjenice, jer se čak 60% preduzeća izjasnilo afirmativno u smilsu uspešnosti primene informacionih tehnologija, oko 30% se slaže delimično, dok samo 10% smatra da ne treba koristiti savremen informaciono-komunikacione tehnologije (Vickery et al, 2019). Veoma važna funkcija informacionih sistema u poslovanju preduzeća jeste mogućnost analize finansijskog poslovanja i u skladu sa tim pravovremeno preduzimanje korektivnih akcija.…”
Section: Informacione Tehnologije U Poslovnim Organizacijamaunclassified
“…On the other hand, entrepreneurship and self-employment can be considered key levers in the fight against mass unemployment. In recent times, as key drivers of cultural and economic development of society, creative entrepreneurs are emerging as carriers of the creative economy that bridge the gap between artists and consumers (Newbigin, 2010;Wagner, 2011;Maryunani & Mirzanti, 2015;Rae, 2004;Vickery, Lavanga & Loots, 2019;HKU (2010); Hausmann & Heinze (2016); Taghi Toghraee & Monjezi, 2017). Table 2 shows an interesting classification of the research on entrepreneurship in the context of the creative industry.…”
Section: Employment Entrepreneurship and Creative Economy -Theoretical Aspectsmentioning
confidence: 99%